2020
DOI: 10.1111/1750-3841.15561
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for black coffee are spread over a wide range of brew strengths and extraction yields

Abstract: Brewing is the final and key step in the production of the coffee beverage. Extraction related metrics such as the total dissolved solids (TDS), percentage extraction yield (PE) of solutes, and brew temperature (BT) are widely believed to govern the flavor and corresponding consumer acceptance of the resulting brew, as summarized in the industry standard “Coffee Brewing Control Chart.” In this study, we investigated how the three factors of TDS, PE, and BT affected consumer acceptance of a medium roast, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 38 publications
0
54
0
1
Order By: Relevance
“…The second dimension was driven by the nutty and smoky attributes on the positive side of the dimension, and bitter, pungent, and fruity on the negative side. The PBAs also contributed to flavours that have been commonly associated with these products and that are not well-liked by consumers in coffee, such as grassy, vegetative, burnt, chemical, and earthy [44][45][46][47]. The participants were segmented into two different consumer groups (dairy consumers and plant consumers) based on if they regularly add dairy products or PBAs to their coffee.…”
Section: Resultsmentioning
confidence: 99%
“…The second dimension was driven by the nutty and smoky attributes on the positive side of the dimension, and bitter, pungent, and fruity on the negative side. The PBAs also contributed to flavours that have been commonly associated with these products and that are not well-liked by consumers in coffee, such as grassy, vegetative, burnt, chemical, and earthy [44][45][46][47]. The participants were segmented into two different consumer groups (dairy consumers and plant consumers) based on if they regularly add dairy products or PBAs to their coffee.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, roasting is another key step in the preparation process of many of the most popular brewed coffee beverages. The roasting step can deliver a pleasant aroma while minimizing the bitterness of the final coffee beverage [ 46 ]. In this study, we have emphasized that all data reported were based on the use of a single-type of wet-washed Arabica coffee beans to prepare coffee beverages with and without roasting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Batali et al has shown that titratable acidity correlates with perceived sourness in brewed coffee, but pH only varies meaningfully between coffees at different roast levels (Batali et al 2021). In contrast, titratable acidity correlates with liking of acidity (Batali et al 2021), and acidity liking is a major driver of difference between consumer cluster preferences of brewed coffee with some consumers reacting very positively and others negatively (Cotter et al 2021).…”
Section: Correlations Between Acid Concentrations and Sensory Quality Of Roasted And Brewed Coffeementioning
confidence: 99%